Perceptions of Marriage and Future Marital Intentions among Filipino Senior University Students - Galit, Jhonnet Kim; Albor, Rufo Gil; Ancho, Inero; Botor, Nephtaly Joel; Sagun, Danica Jae; Ledesma, Jamella Michaella Ezra; Mendres, Mark Yvanne; Gironella, Elaijah Andrea (Journal of Family Sciences, 2025)
Entering marriage is a significant life decision that includes major transitions in one's life. The study investigated the perceptions of marriage among Filipino senior university students majoring in Human and Family Development at a university in the Philippines. It aimed to understand their definition and views of marriage, and the factors that influence their decision to get married. The study employed a two-step descriptive qualitative design, combining initial surveys to identify themes, followed by in-depth interviews for deeper exploration, and purposive sampling to select eight senior students aged 20-22 years old from the University of the Philippines Los Baños in 2019, whose responses were analyzed using thematic analysis. Findings revealed that participants define marriage as a lifelong commitment to another person that is legally recognized and strengthened by intimacy. While they viewed marriage as a personal choice, they acknowledged its legal benefits, such as legitimate recognition of their children. Five key factors emerged in their decision to marry: influence of media, family pressure, financial capability, achievement of personal goals, and desire to build their own family. These findings reflect the negotiation between traditional family values and the modern aspirations of the younger generation in the Philippines. The study offers valuable insights for developing culturally-responsive relationship education programs for Filipino students and informing family-oriented policies that address the evolving perspectives of early adults toward marriage.